Evaluation of Epidemiological and Genetic Risk Factors Associated with Idiopathic Congenital Talipes Equinovarus in the South Indian Population (GAIMS Journal of Medical Sciences, 2023)
Background: The heterogeneity between studies in reported risk factors for Congenital Talipes Equinovarus (CTEV) may be due to many factors including definitions of CTEV, whether non-idiopathic cases are included, differences in study design, and chance as some series are relatively small. This study was aimed to evaluate epidemiological and genetic risk factors associated with Idiopathic Congenital Talipes Equinovarus (ICTEV) in a south Indian Population.Methods: A prospective case parental control design - epidemiological data was collected in the form of factors associated with mother like age at index pregnancy, education, reproductive history, smoking history. Similarly for father we studied factors like age, education, alcohol intake and genetic risk factors mainly MTHFR C677C>T Gene polymorphism. Clinically severity graded by dimeglio scoring system and classified accordingly.Results: Total 145 Case Parent triads were evaluated over a period of three years duration. Around 74 percent of ICTEV cases were males with positive family history. Positive association is found with first pregnancy, C – section, bilaterality, mother’s education, father’s alcohol intake during index pregnancy. There was negative association with increasing number of mutant T allele and severity of disease.Conclusions: Our study is first study to show MTHFR C677C>T gene polymorphism and its protective role in ICTEV in an Indian population and also given an epidemiological picture of a large series of children in south India. There is a need of increasing awareness of folic acid use during index pregnancy and fortification of food with folic acid in national level programmes.